PENGEMBANGAN DESAIN USER EXPERIENCE (UX) PADA WEBSITE KECAP SEGI TIGA MAJALENGKA - Permana, Sri Mentari Widya Ningrum; Mardiana, Ardi (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2025)
The rapid development of digital technology has encouraged companies to utilize websites as a medium for promotion and branding. This study focuses on the development of user experience (UX) and user interface (UI) design for the Segi Tiga Soy Sauce website, which previously had limited digital presence and promotional reach. The objective of this research is to design a responsive, modern, and user-friendly website that improves customer engagement and supports the company’s business growth. The research applies the Design Sprint method, consisting of five stages: understand, diverge, decide, prototype, and validate. Data collection was conducted through interviews, observation, and literature studies to identify user needs and business requirements. The design process produced wireframes, storyboards, and prototypes using Figma, followed by usability testing with 20 respondents. The evaluation results using the System Usability Scale (SUS) showed a score of 87, indicating high user satisfaction and effective usability. The findings demonstrate that the proposed design not only enhances branding and professionalism but also improves market reach and communication efficiency for the company. This research highlights the importance of integrating UX principles in website development to achieve both functional and aesthetic goals in digital business promotion.